Comparative Studies on CO2 Adsorption Kinetics by Solid Adsorbents. (December 2016) - Singh, Vinod Kumar; Kumar, E. Anil
Abstract: Adsorption kinetics of carbon dioxide (CO2 ) on activated carbon (Norit RB3 type steam activated rod) and zeolite 5A (Si/Al = 1.33) are compared at various temperatures (298, 308, 318 and 338K) and supply pressures (1, 5, 10 and 20bar). Sievert's type experimental setup is used for adsorption kinetics measurement. The experimental data is subsequently modelled using pseudo first and second order kinetics models, which revealed that the pseudo second order kinetics model well fitted the CO2 adsorption kinetics data than pseudo first order kinetics model. The rate constants and activation energies of CO2 adsorption on activated carbon and zeolite 5A are estimated. It is found that at 1bar supply pressure, the rate of CO2 adsorption on zeolite 5A is more than that of the activated carbon, while at higher pressure, the rate of CO2 adsorption on the activated carbon is greater than the zeolite 5A due to large surface area and pore volume. Activation energies are calculated at different pressures by fitting the Arrhenius equation to the adsorption kinetics data. It is observed that the activation energies of activated carbon are slightly more than that of the zeolite 5A.